A Quick Guide to Quantitative Research in the Social Sciences - Davies, Christine (Open textbook library., 2021)
This resource is intended as an easy-to-use guide for anyone who needs some quick and simple advice on quantitative aspects of research in social sciences, covering subjects such as education, sociology, business, nursing. If you area qualitative researcher who needs to venture into the world of numbers, or a student instructed to undertake a quantitative research project despite a hatred for maths, then this booklet should be a real help. The booklet was amended in 2022 to take into account previous review comments.